PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG (STUDI KASUS PADA E-CINEMA ENTERTAINMENT PLAZA SEMARANG) - Brian Ramaputra; Agus Hermani D.S. (Jurnal Ilmu Administrasi Bisnis, 2018)
E-Plaza Cinema Semarang, as a cinema services company, can be found a low amount of repurchase intention, which causing the capacity of the cinema is often not fulfilled and also causing the ticket sales per year target is not achieved. It is presumably caused by the inadequate quality of its products (film) and its poorly-rated service. This study is tailored to reveal how the quality of its products (film) and service can influence consumers repurchase intention towards E-Plaza Cinema Semarang. Explanatory Research is the research type that is used in this study. The verdict of this study conveys that both of the product quality and service quality variables have positive, solid, and notable influences regarding to consumers repurchase intention. Purposive Sampling is chosen to be used in 100 respondents. This study used questionnaire instrument in Likert Scale to collect data. The data analysis methods that are used in this study are Validity and Reliability Test, Correlation Coefficient (R), Regression Test, Coefficient of Determination (R2), T Test, and F Test. Two variables, which have been assessed concurrently and progressively, reveal that the product quality variable and the service quality variable simultaneously have a significant, positive and solid correlation toward the consumers repurchase intention variable. Therefore, if product quality and service quality are increased then it will also increase consumers repurchase intention, and if product quality and service quality are decreased then the consumers repurchase intention will also decreased and it can be found that service quality has bigger effect than product (film) quality towards consumers repurchase intention. Suggestions that can be given to increase the consumers repurchase intention is to improve product quality and service quality of E-Plaza Semarang which is considered important for the consumers but has a low attention from E-Plaza such as actors/actress popularity, attitudes and abilities of employees, movie image quality, the duration of movie, movie show times, and the safety inside E-Plaza.